Association of SNP (RS4880) in SOD-2 Gene with Diabetic Nephropathy - Umar, Sana; Yousaf, Javad; Rashid, Amir; Majeed, Asifa; Shah, Syed Zubair Hussain (Pakistan Armed Forces Medical Journal, 2023)
Objective: To find an association between SNP (rs4880) in SOD-2 gene with Diabetic Nephropathy. Study Design: Case Control Study.Place & Duration of study: Department of Biochemistry and Molecular Biology, Army Medical College Rawalpindi and Armed Forces Institute of Urology, Rawalpindi Pakistan, from Nov 2020 to Mar 2021.Methodology: A total of 60 people were enrolled including 30 healthy individuals and 30 patients of diabetic nephropathy. Both males and females aged 35-85 years were enrolled. Baseline biochemical tests were performed to ascertain diagnosis and exclude comorbidities. DNA was extracted using kit method and sequence of interest was amplified using PCR. Amplified product of genomic DNA of each individual was subjected to restriction fragment length polymorphism (RFLP) analysis. Data was analyzed using SPSS version 22. Results: The frequency of TT genotype (40%) was higher among type 2 Diabetes Mellitus (T2DM) patients with nephropathy than CT (33.3%) and CC (26.6%) genotypes however the odds ratio for TT with 95% confidence interval (CI) was 2.53(0.69- 9.25) with p=0.35 which is statistically non-significant. The association value for genotypes was 1.29 (p-value=0.52) hence not significant.Conclusion: There was no significant association present between SNP (rs4880) in SOD-2 gene which causes Val16Ala polymorphism in superoxide dismutase 2 gene, with nephropathy in type 2 Diabetes Mellitus (T2DM) patients.